Recognition Memory in Noonan Syndrome - Floriana Costanzo; Paolo Alfieri; Cristina Caciolo; Paola Bergonzini; Francesca Perrino; Giuseppe Zampino; Chiara Leoni; Deny Menghini; Maria Cristina Digilio; Marco Tartaglia; Stefano Vicari; Giovanni Augusto Carlesimo (Brain Sciences, 2021)
Noonan syndrome (NS) and the clinically related NS with multiple lentiginous (NMLS) are genetic conditions characterized by upregulated RAS mitogen activated protein kinase (RAS–MAPK) signaling, which is known to impact hippocampus-dependent memory formation and consolidation. The aim of the present study was to provide a detailed characterization of the recognition memory of children and adolescents with NS/NMLS. We compared 18 children and adolescents affected by NS and NMLS with 22 typically developing (TD) children, matched for chronological age and non-verbal Intelligence Quotient (IQ), in two different experimental paradigms, to assess familiarity and recollection: a Process Dissociation Procedure (PDP) and a Task Dissociation Procedure (TDP). Differences in verbal skills between groups, as well as chronological age, were considered in the analysis. Participants with NS and NSML showed reduced recollection in the PDP and impaired associative recognition in the TDP, compared to controls. These results indicate poor recollection in the recognition memory of participants with NS and NSML, which cannot be explained by intellectual disability or language deficits. These results provide evidence of the role of mutations impacting RAS–MAPK signaling in the disruption of hippocampal memory formation and consolidation.